Situation of Farm Condition of Raising Livestock as a Commodity for Farmers in Nan District, Luang Prabang Province - Anongsith, Sonenaly; Chanthakhoun, Vongpasith; Kandee, Thanousinh (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study was conducted in farmers who raised animal as a commodity in Nan District, Luang Prabang Province. The quantitative method to collect data by using a questionnaire of 180 farmers, the data were analyzed by SPSS version 25. The results were found that 73.9% was male, 46.7% was Lao ethnic group, 31.1% age between 42-49, 73.9% were graduate in primary school level, 98.3% were married, 58.9% family had members between 6-10 people, family income per year were low than 60 million with 81.7%, the income from raising animal more than 20 million cover 92.2%. Famer who had an experience in animal raising morthan 7 years, 61.7% of animals raised are cattle, followed by 48.9% of pigs, 39.5% of goats, and only buffalo 17.2%. The model of animal raised was most in free range (63.3%), with an average area of ​​3.71 hectares/family, the feeding model was grazing (54.4%). In the condition of animal husbandry management was show that unable to access funding sources was low level with the Mean = 1.84; SD = 0.26 the ability to access veterinary services was determined was medium level with the Mean = 3.28; SD = 0.55, however receiving support for animal husbandry from various sectors was low level with the Mean = 1.78; SD = 0.72 Access to animal husbandry knowledge sources was medium level with the Mean = 2.93; SD = 0.71 Market operations for animal products are rated as good with the Mean = 3.76; SD = 0.69, compliance with documents for establishing farms appears to be relatively low with the Mean = 1.13; SD = 0.70. The conclusion that most of the animal husbandry of farmers is still a natural farm, lack of care and attention according to technical principles, access to sources of information on animal husbandry were low.